2016
DOI: 10.1007/s00784-016-1985-y
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of obstructive sleep apnea in children with Robin sequence, a cross-sectional study

Abstract: ObjectiveThe objective of this cross-sectional study is to assess the prevalence, course, and management of obstructive sleep apnea (OSA) in children with Robin sequence (RS) aged 1–18 years.Materials and methodsA cross-sectional study was conducted in 63 children aged 1 to18 years with RS. Patient data were collected on baseline characteristics and management. OSA was evaluated by polysomnography.ResultsSixty-three children with RS were included (median age 8.0 years) and divided into two groups based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This is in line with Van Lieshout et al, who reported that, between the age of 1 and 18 years, almost one out of four RS infants continues to have respiratory problems. Additionally, RS infants who need respiratory support early after birth are at risk of continuing or re-developing obstructive sleep apnea after the age of 1 year [ 34 ]. In our study, we could relate the cause of respiratory insufficiency to upper airway obstruction in only two infants (VII and IX).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with Van Lieshout et al, who reported that, between the age of 1 and 18 years, almost one out of four RS infants continues to have respiratory problems. Additionally, RS infants who need respiratory support early after birth are at risk of continuing or re-developing obstructive sleep apnea after the age of 1 year [ 34 ]. In our study, we could relate the cause of respiratory insufficiency to upper airway obstruction in only two infants (VII and IX).…”
Section: Discussionmentioning
confidence: 99%
“…Children with PRS, who needed respiratory support early after birth, were at risk of continuing or re-developing OSA after the age of 1 year. Between the age of 1 and 18 years, almost one out of four children with PRS had respiratory problems (83). International guidelines recommended the surgical management of children with PRS who failed conservative therapy (65).…”
Section: Pierre-robin Sequence/syndromementioning
confidence: 99%
“…PRS infants often require early and longterm upper airway management (65). Those who needed respiratory support at an early age looked for careful monitoring until adulthood (83).…”
Section: Pierre-robin Sequence/syndromementioning
confidence: 99%
“… 39 Another study found that of the 7 isolated RS-patients that underwent a superiorly based pharyngeal flap for VPI, 6 developed OSA and subsequently required flap take-down. 40 Apart from the effect of secondary speech operations on the RS airway, our follow-up data on OSA, together those from another study, 41 indicate the importance of continued monitoring of at-risk RS-patients beyond infancy.…”
Section: Discussionmentioning
confidence: 53%